Digital Infrastructure Management and Student Learning Motivation: Evidence from a Quasi-Experimental Study in Secondary Education - Tanti Harjanti; Wiwik Pudjaningsih (Kelola: Jurnal Manajemen Pendidikan, 2026)
This study investigates the effect of Digital Infrastructure Management (DIM) on student learning motivation in secondary education using a quasi-experimental design. Although previous studies have widely examined educational technology usage, limited research has explored digital infrastructure management as a structured organizational intervention influencing motivational outcomes. Addressing this gap, the present study conceptualizes DIM as a systematic managerial process involving planning, organizing, maintenance, and monitoring of digital learning resources. A non-equivalent control-group pretest–posttest design was employed involving 76 Grade VIII students divided into experimental and control groups. The experimental group received structured DIM implementation, while the control group continued conventional digital practices. Data were collected using a validated learning motivation questionnaire and analyzed through descriptive statistics, paired and independent-samples t-tests, and Pearson correlation analysis. The findings revealed a significant increase in student motivation in the experimental group (p < 0.001), whereas the control group showed no meaningful change. Posttest comparisons indicated a statistically significant difference between groups with a large effect size (d = 1.98). Furthermore, DIM implementation quality demonstrated a strong positive correlation with student motivation (r = 0.742). These findings suggest that structured digital governance may function as an enabling organizational mechanism for enhancing motivation in digitally supported learning environments. The study contributes theoretically by extending discussions on digital transformation beyond technology adoption toward institutional management processes, while practically informing school leaders and policymakers about the importance of sustainable digital infrastructure governance in secondary education.